2022
DOI: 10.1097/j.pain.0000000000002773
|View full text |Cite
|
Sign up to set email alerts
|

Consistent pattern between physical activity measures and chronic pain levels: the Tromsø Study 2015 to 2016

Abstract: Epidemiological literature on the relationship between physical activity and chronic pain is scarce and inconsistent. Hence, our aim was to assess the relationship applying comprehensive methodology, including self-reported and accelerometer measures of physical activity and different severity levels of chronic pain. We used data from the Tromsø Study (2015Study ( -2016. All residents in the municipality, aged 40 years and older were invited to participate (n 5 32,591, 51% women). A total of 21,083 (53%) women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
2
3
0
Order By: Relevance
“…The reason for this result may be ethnic differences in endogenous pain regulatory mechanisms, and the types of moderate and vigorous activity are different among different racial populations [29]; thus, a higher number of days/week with ≥10 min of moderate and vigorous physical activity has a negative impact on CP in Europeans. Our results showing that physical activity is beneficial for African Americans and Afro-Caribbean individuals coincide with studies showing that physical activity reduces chronic pain [45][46][47]. However, with the frequent economic and cultural interaction of the world, the migration of people today has produced ancestral variation between populations and on the genome within individuals [48].…”
Section: Discussionsupporting
confidence: 87%
“…The reason for this result may be ethnic differences in endogenous pain regulatory mechanisms, and the types of moderate and vigorous activity are different among different racial populations [29]; thus, a higher number of days/week with ≥10 min of moderate and vigorous physical activity has a negative impact on CP in Europeans. Our results showing that physical activity is beneficial for African Americans and Afro-Caribbean individuals coincide with studies showing that physical activity reduces chronic pain [45][46][47]. However, with the frequent economic and cultural interaction of the world, the migration of people today has produced ancestral variation between populations and on the genome within individuals [48].…”
Section: Discussionsupporting
confidence: 87%
“…However, future studies should focus on evaluating what type of physical activity would be most beneficial for HRQOL and well-being, especially in people who may already have some physical limitations due to co-morbidities. Our findings on the importance of pain also align with our findings of the importance of physical activity, which can be used as prevention against pain [32], but also against early retirement and sick leave, which were important within the employment factor. With our study's findings in mind, we suggest a research focus on the prevention of pain in and before (throughout life) in middle age to increase the chances of a life free from pain in later ages.…”
Section: Plos Onesupporting
confidence: 88%
“…Previous research in patients with CLBP have shown that motor and problem-solving skill exercises work well in improving cognitive impairment ( 21 23 ). Furthermore, increased activity has shown to correlate negatively with the chronic pain, and the movement velocity has shown to correlate with functional recovery in chronic pain ( 24 , 25 ). Thus, we used an assumption that the time spent on a given activity correlates with the condition of a participant, i.e., a healthy participant would finish the activities faster than a participant with CLBP.…”
Section: Methodsmentioning
confidence: 99%